Effects of heat treatment on microstructure and properties of CrVNiAlCu high-entropy alloy - Bai Shijie; Xiao Yifeng; Wu Liang; Zhang Qiankun (High Temperature Materials and Processes)
This study employs X-ray diffraction, scanning electron microscopy, electrochemical workstations, and hardness testers to evaluate the impact of annealing temperatures (600, 700, and 800°C) on the microstructure and corrosion resistance of the CrVNiAlCu high-entropy alloy. Findings demonstrate that the as-cast alloy is composed of copper-rich FCC and chromium-rich BCC phases. With increasing annealing temperatures, the alloy’s crystals transform into dendritic structures, accompanied by the precipitation of new phases. The as-cast alloy displays a peak hardness of 674 HV, which significantly reduces after annealing. Moreover, annealing treatment reduces lattice distortion and element segregation in the alloy, thereby improving the corrosion resistance of the alloy. Importantly, the alloy attains its highest corrosion resistance after annealing at 800°C.